Social Media Influencer Credibility and Brand Image on Purchase Intention in Modest Fashion: The Moderating Role of Islamic Religiosity - Xaviera, Yasmin Alif; Effendi, Jaenal; Jahroh, Siti (Indonesian Journal of Business and Entrepreneurship, 2026)
Background: The rapid expansion of social media has significantly transformed marketing communication and consumer purchasing behavior. Social media platforms enable brands to reach consumers more effectively through influencer marketing, which has become a prominent promotional strategy in the fashion industry. One segment experiencing substantial growth is modest fashion, which is closely associated with Muslim values while also appealing to a wider consumer base. In Indonesia, the modest fashion industry continues to develop alongside the influence of social media influencers (SMIs). Purpose: This study aims to investigate the influence of social media influencer (SMI) credibility and brand image on purchase intention in the modest fashion industry. In addition, this study examines the moderating role of Islamic religiosity in the relationship between SMI credibility and purchase intention, as well as between brand image and purchase intention. Design/methodology/approach: This study employs a quantitative research approach. Data were collected through an online questionnaire distributed to 300 Muslim women in Indonesia who actively follow modest fashion influencers on social media platforms, particularly Instagram and TikTok. Respondents were selected using purposive sampling to ensure relevance to the research context. The data were analyzed using Partial Least Squares–Structural Equation Modeling (SEM-PLS) with SmartPLS 4, following measurement and structural model evaluations to test the proposed hypotheses and moderation effects. Findings/Result: The results indicate that SMI credibility and brand image have a significant positive effect on purchase intention. Among the dimensions of SMI credibility, perceived expertise is identified as the strongest predictor of purchase intention, suggesting that consumers place high importance on influencers’ knowledge and competence in modest fashion. Brand image also significantly influences purchase intention, with innovation emerging as the most dominant dimension. Furthermore, Islamic religiosity is found to have a significant direct effect on purchase intention. The moderation analysis shows that Islamic religiosity strengthens the relationship between SMI credibility and purchase intention, as well as between brand image and purchase intention. Conclusion: This study concludes that SMI credibility and brand image play a crucial role in shaping consumers purchase intention toward modest fashion products. Islamic religiosity enhances these relationships, indicating that consumers with higher religiosity levels are more responsive to credible influencers and positive brand perceptions. Originality/value (State of the art): This study contributes to the literature by providing empirical evidence on the moderating role of Islamic religiosity in influencer marketing within the modest fashion context. The findings extend existing purchase intention models by integrating cultural and religious dimensions, offering both theoretical and managerial insights. Keywords: online shopping, influencer marketing, perceived expertise, perceived trustworthiness, brand innovation